The Use of Kickboard and Pull Buoy Aid Toward Freestyle Swimming Speed in Children Aged 6-9 Year at Club Aura Swimming Academy - Maysha Alya Rahmadianti; Fatkur (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study was motivated by the importance of mastering basic freestyle swimming techniques in early childhood, particularly toimprove speed through better leg movement, arm movement, and body position. Intial observations at Club Aura Swimming Academy indicated that most students aged 6-9 years still exhibited weak kicking techniques and poor movement coordination, which negatively affected their freestyle swimming speed. Therefore, the use of assistive devices such as kickboards and pull buoys was considered effective in helping students practice specific movement components in a more focused and gradual manner. The purpose of this study was to determine the effect of kickboards and pull buoys on freestyle swimming speed among children aged 6-9 years at Club Aura Swimming Academy. A pre-experimental method with one-group pretests/posttest design was employed, inloving a sample of 10 students slected through purposive sampling. The research instrument was a 25-meter freestyle swimming time test, and data were analyzed using the ShapiroWilk normality test and a paired sample t-test to examine differences before and after the treatment. The results revealed a significant improvements in students swimming speed, with the average pretests time of 51.54 seconds decreasing to 48.99 seconds in the posttests. Furthermore, the paired sample t-test produced a significant value of 0.000 (<0.05), indicating that the use of kickboards and pull buoys had a significant effect on improving freestyle swimming speed.